Produção de mudas de bambu Guadua angustifolia Kunth (Poaceae) por propagação vegetativa - Fonseca, Fernanda Karina Pereira da (2007)
The bamboo is a tropical, renewable, perennial culture of fast growth and with several uses. However, its use and research is moistly restricted to Asian countries. In Brazil the demand for bamboo has increased in the last years. From November 2005 to September 2006, experiments were carried out with the objective to evaluate the ability of Guadua angustifolia to produce new plants from cuttings of secondary branches and clump division of two years seedlings. There were evaluated the sprouting and rooting capacity of cuttings with 1, 2 or 3 nodes that had been collected from secondary branches of the apical, middle or basal parts of the bamboo plants. It was also evaluated the effect of 0,500,1000 and 1500 mg. Kg -1 de AIB applied on the cuttings planted in sand, coconut fiber or a compost formed by sand + coconut fiber + soil (1:1:1). The multiplication rate of the shoots was not influenced by the cuttings planting position, the presence of leaves or cuttings density on the planting trays. The horizontal position of the planting cuttings increased the shoot and root length. Cuttings of 2 and 3 nodes collected from the basal and middle parts of the bamboo presented greater capacity of shooting and rooting growth. The concentrations of AIB and planting bed material did not influenced the development of roots and shoots in the cuttings.